Aspekty technologiczne produkcji piwa a funkcjonowanie systemu zarządzania jakością w browarze - Wójcik, Agnieszka; Lesiów, Tomasz (Technological Aspects of Beer Production Versus Quality Management System : in a Brewery, 2007)
The aim of the paper is to present functioning of the Quality Management System ISO 9001 in one of the leading breweries with an old tradition of brewing and modern technological background as well as to show quality improvement directions taking into account human factor as a main element influencing the quality. It has been proven that in the company the quality is created by processes, systems and mainly all workers, therefore activities in the range of improvements should comprise the humanistic sphere of company functioning. Skilled labour is an important link and factor in connecting the modern technology with properly working quality management system to satisfy all customer requirements and expectations concerning the final product.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Technologia (12); 2007; nr 1172, s. 80-102